Modified super absorbent resin ice crystal, light marine concrete doped with modified super absorbent resin ice crystal and preparation method of light marine concrete

By doping modified highly absorbent resin ice crystals in offshore concrete, the closed holes and enhanced hole wall strength is solved, and the compressive strength and durability of offshore concrete is difficult to guarantee when reducing bulk weight, and lightweight offshore concrete is achieved that meets the requirements of seaport engineering.

CN119874244APending Publication Date: 2025-04-25XIAMEN TIANRUN JINLONG BUILDING MATERIAL +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411912829.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing offshore concrete is difficult to ensure compressive strength and durability while reducing the bulk weight, and cannot meet the requirements of seaport engineering.

Method used

Modified highly absorbent resin ice crystals are used to form ice crystals by absorbing water and expanding through the water absorption and expansion of the highly absorbent resin particles. They are adsorbed by modifiers to form ice crystals with surface adsorption and modification, and doped into concrete to construct closed holes and enhance the strength of the hole wall.

Benefits of technology

It has achieved the reduction of the weight of offshore concrete while improving its compressive strength and durability, meeting the requirements of seaport engineering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, in particular to modified super absorbent resin ice crystals, light marine concrete doped with the modified super absorbent resin ice crystals and a preparation method of the light marine concrete. The modified super absorbent resin ice crystal provided by the invention can form uniformly distributed closed holes in concrete, strengthen the hole wall strength and reduce the strength loss caused by pore forming. The invention further provides the light marine concrete doped with the modified super absorbent resin ice crystals, the modified super absorbent resin ice crystals and the high-performance air entraining agent are doped to form pores in the concrete, the volume weight of the concrete is effectively reduced, and the compressive strength, durability and other properties still meet the design requirements. The invention further provides a preparation method of the light marine concrete doped with the modified super absorbent resin ice crystals, vibration rolling forming is matched with steam curing to optimize the preparation process, it is ensured that internal materials are tightly connected, internal hardening of slurry is accelerated, micropores are formed in the modified super absorbent resin ice crystals earlier, a cementing material is activated, and the concrete performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a modified highly water-absorbent resin ice crystal, a lightweight marine engineering concrete doped with the modified highly water-absorbent resin ice crystal, and a preparation method thereof. Background Art

[0002] With the continuous development of port engineering construction in my country, the scale of seaports has continued to expand, the trend of offshore and deep-water ports has continued to strengthen, the requirements for structural durability have continued to increase, and the use of high-performance marine concrete has also increased year by year.

[0003] During the construction of various projects, these facilities are usually in a seawater environment. The chloride ion erosion in seawater and the freezing and thawing of seawater can cause the steel bars in the concrete to rust, resulting in concrete cracking, spalling and steel bar breakage, reducing the mechanical properties of the structure. In addition, most concrete structures weigh tens of thousands of tons, which increases the difficulty of transportation and installation. Therefore, marine engineering concrete should have the characteristics of high strength, strong corrosion resistance, good durability, and light weight, and at the same time meet the requirements of economy.

[0004] To solve the above problems, the existing technology reduces the concrete bulk density by adding air entraining agents, and improves the chloride ion penetration resistance and frost resistance, and the cost is low. However, the air entraining agent will cause the concrete strength to decrease. When the air content exceeds 10%, the impact on the concrete strength will exceed 50%. Therefore, how to reduce the bulk density of marine engineering concrete while ensuring that its compressive strength and durability meet the requirements of port engineering is still a technical problem that technicians in this field are committed to solving. Summary of the invention

[0005] In order to solve the technical problem of how to reduce the bulk density of marine engineering concrete while ensuring that its compressive strength and durability meet the requirements of port engineering, the present invention provides a modified super absorbent resin ice crystal, which is prepared by super absorbent resin particles absorbing water and expanding, then freezing to form ice crystals, and then adsorbing and modifying with a modifier; The ratio of the super absorbent resin, deionized water and modifier by weight is (2-5): (500-1200): (5-12), wherein only the weight of the deionized water and modifier absorbed and adsorbed by the super absorbent resin is calculated; The modifier is obtained by mixing an anionic surfactant, an interfacial enhancer and nano-silicon dioxide in a weight ratio of (0.1-0.5): (100-300): (1-10); The modified super absorbent resin ice crystals are mixed into concrete, and closed pores are constructed inside the concrete, so that the bulk density of marine engineering concrete can be reduced. At the same time, a modifier is attached to the surface of the modified super absorbent resin ice crystals, which can act on the concrete pore wall to enhance the pore wall strength, thereby ensuring that the compressive strength and durability of the marine engineering concrete meet the requirements of port engineering.

[0006] In one embodiment, the particle size of the super absorbent resin particles is 0.01~1 mm; the anionic surfactant is any one of sodium dodecyl sulfate, sodium dodecyl polyoxyethylene ether sulfate and sodium α-olefin sulfonate, with a solid content of 0.2%~0.7%; the interface enhancer is an emulsion-type interface enhancer or a solution-type interface enhancer; the particle size of the nano-silica is 50~100 nm, and the purity is ≥98%.

[0007] In one embodiment, the modified super absorbent resin ice crystal preparation process is: S100, pouring the super absorbent resin particles into deionized water and stirring them sufficiently to allow them to fully absorb water and swell to obtain a solution with a gel, and separating and removing the remaining deionized water in the solution to obtain a super absorbent resin gel; S101, in a low-temperature laboratory at room temperature of -5 to 0°C, evenly spread the super absorbent resin gel on the surface of a fine grid, put it into a freezing device and freeze it for 6 to 10 hours, and after the freezing, perform mechanical vibration dispersion to obtain super absorbent resin ice crystals; S102. In a low-temperature laboratory at a room temperature of -5 to 0°C, pour the super absorbent resin ice crystals into a modifier, rotate and stir for 2 to 10 minutes, and filter to obtain the modified super absorbent resin ice crystals.

[0008] Furthermore, in step S100, the ratio of the addition amount of the super absorbent resin particles to the deionized water is (2-5): (1200-2000) in parts by weight; in step S102, the ratio of the addition amount of the super absorbent resin ice crystals to the modifier is (1-5): (3-10) in parts by weight.

[0009] The present invention also provides a method for preparing lightweight marine engineering concrete using modified super absorbent resin ice crystals doped with modified super absorbent resin ice crystals as described above, comprising the following steps: S200. In a low-temperature laboratory at a room temperature of -5 to 0°C, cement, ultrafine powder and stone powder are mixed uniformly by weight to obtain a mixture A, coarse aggregate and fine aggregate are mixed uniformly to obtain a mixture B, a high-performance water reducing agent, a high-performance air entraining agent and water are mixed uniformly to obtain a mixed solution C, and modified superabsorbent resin ice crystals are weighed; S201. In a low-temperature laboratory at a room temperature of -5 to 0°C, mix mixture A and mixture B, stir for 10 to 30 seconds, then pour into mixture C, stir for 180 to 240 seconds, and finally pour into modified superabsorbent resin ice crystals, stir for 20 to 40 seconds to obtain a mixture with an expansion range of 450 to 500 mm; S202. In a low-temperature laboratory at a room temperature of -5 to 0°C, pour the mixture into a fixed mold, vibrate and roll it, seal the upper layer with a film, and after hardening, put it into a steam curing box at 80 to 90°C for curing for 0.5 to 1 day with the mold, and then place it in a natural environment for curing to obtain the lightweight marine concrete doped with modified highly absorbent resin ice crystals.

[0010] In one embodiment, the distribution ratio of each group is as follows according to weight parts: 270~350 parts of cement 45~70 parts of modified super absorbent resin ice crystal Ultrafine powder 150~200 parts 20~30 parts of stone powder Coarse aggregate 700~800 parts Fine aggregate 700~800 parts High performance water reducing agent 5~11 parts High performance air entraining agent 0.6~2 parts 125~140 parts of water.

[0011] In one embodiment, the cement is any one of P·O 42.5R cement, P·O 52.5 cement and P·II 52.5 cement; the ultrafine powder is a mixed and refined product of multiple mineral admixtures after grinding, and the particle size is 0.1-30 μm, and the mineral admixture is any two or a combination of any several of fly ash, slag powder, silica fume and microbeads; the stone powder is any one or a combination of any several of limestone powder, marble powder, granite powder and ceramic polishing powder, and the calcium carbonate content of the stone powder is 82%-87%, the fineness is 8%-13%, the 28d activity index is 80%-95%, and the fluidity ratio is 97%-103%; the coarse aggregate is any one or a combination of any several of crushed stone with a particle size of 5-10 mm, crushed stone with a particle size of 5-16 mm, crushed stone with a particle size of 5-20 mm, and crushed stone with a particle size of 10-20 mm, and the apparent density of the coarse aggregate is 2650-2670 kg / m 3 The porosity is 39%~42%, and the crushing value is 2%~4%; the fine aggregate is machine-made sand, with a fineness modulus of 2.5~2.8 and an apparent density of 2590~2630 kg / m 3 The porosity is 40%~44% and the crushing value is 20%~25%.

[0012] In one embodiment, the high-performance water reducer is compounded from a polycarboxylic acid viscosity-reducing water-reducing concentrate, a slump-retaining agent, cellulose, a coagulant, a regulator and water, and has a solid content of 12% to 15%, a water reduction rate of 25% to 30%, and a 28d compressive strength ratio of 140% to 150%.

[0013] In one embodiment, the high-performance air entraining agent is any one of anionic air entraining agent, cationic air entraining agent, non-ionic air entraining agent and amphoteric air entraining agent, or a combination of any several of them.

[0014] The present invention also provides a lightweight marine engineering concrete doped with modified super absorbent resin ice crystals, which is prepared by the preparation method of the lightweight marine engineering concrete doped with modified super absorbent resin ice crystals as described in any one of the above items.

[0015] The modified super absorbent resin ice crystal provided by the present invention is made into an ice crystal structure by super absorbent resin particles and mixed into concrete, so that it can be evenly distributed inside the concrete and form closed pores, and the ice crystal structure can slowly release water, so that the slurry structure inside the concrete is fully hydrated, but it will not lose a lot of water due to the strong alkaline cement slurry system, and the water-cement ratio inside the concrete is maintained at a stable low level, achieving the effect of reducing the concrete bulk density, and effectively solving the problem of high apparent density of concrete.

[0016] The modified super absorbent resin ice crystal provided by the present invention has a modifying material attached to the surface of the ice crystal, and the modifying material includes an anionic surfactant, an interface enhancer and nano silicon dioxide; wherein the interface enhancer has strong interface permeability, can be combined with the concrete pore wall to form a hard crystalline film, thereby enhancing the concrete interface strength; the specific surface area of ​​the nano silicon dioxide is usually hundreds or thousands of times that of cement particles, so a huge number of crystal nuclei can be provided at a lower dosage, which can greatly accelerate the crystallization and growth rate of cement hydration products, and increase the uniformity and compactness of the hydration products; and the anionic surfactant acts as a dispersant to disperse the nano silicon dioxide, reduce its agglomeration in the interface enhancer, and make it uniformly dispersed; the above three act synergistically, adhere to the surface of the modified super absorbent resin ice crystal and contact with the pore surface, comprehensively enhance the pore wall strength, thereby improving the mechanical properties and durability of the concrete.

[0017] The lightweight marine engineering concrete doped with modified super absorbent resin ice crystals provided by the present invention constructs closed pores in the concrete by adding modified super absorbent resin ice crystals and high-performance air entraining agent to achieve the effect of reducing the concrete bulk density and solve the problem of high apparent density of concrete; further, compared with ordinary super absorbent resin that has only been pre-absorbed, the ice-crystallized super absorbent resin can exist in the concrete for a longer time, is not easily affected by the strong alkaline cement paste in the concrete and releases water too early and too quickly, but slowly releases water according to its internal hydration heat, and the size of the pore structure constructed by it is larger than the size of the pores that can be constructed by ordinary super absorbent resin that has been pre-absorbed, so the effect of reducing the concrete bulk density is more significant; in addition, because the present invention specifically adopts modified super absorbent resin ice crystals with a modifier attached to the surface, the modifier can act on the micropore wall to enhance the pore wall strength, thereby effectively reducing the inevitable loss of compressive strength and durability performance when reducing the bulk density of marine engineering concrete by pore making, so that it can still meet the requirements of seaport engineering.

[0018] The lightweight marine engineering concrete doped with modified superabsorbent resin ice crystals provided by the present invention particularly adopts a high-performance water-reducing agent as one of the raw material components. The high-performance water-reducing agent has a strong dispersing effect on cementitious materials, can significantly reduce the slurry viscosity, and is particularly suitable for concrete with a low water-cement ratio; in addition, a high-performance air-entraining agent is also particularly adopted. The high-performance air-entraining agent can introduce fine bubbles into the concrete, and less foaming is generated when stirring in the polycarboxylic acid water-reducing agent, which is convenient for mixing the two. Furthermore, because the bubbles introduced into the concrete are fine and uniform, it is not easy to form interconnected large pores, so that the influence of air entrainment and pore formation on the performance of the concrete can be controlled.

[0019] The method for preparing lightweight marine engineering concrete doped with modified super absorbent resin ice crystals provided by the present invention adopts vibration roller forming in combination with steam curing to optimize the preparation process, wherein the vibration roller forming can ensure that the internal materials are tightly connected, and the steam curing can accelerate the hardening of the inside of the slurry, so that the modified super absorbent resin ice crystals form tiny holes earlier, and achieve the effect of activating various cementitious materials, thereby improving the performance of concrete.

[0020] In summary, compared with the prior art, the modified super absorbent resin ice crystals, the lightweight marine engineering concrete doped with modified super absorbent resin ice crystals and the preparation method thereof provided by the present invention, add modified super absorbent resin ice crystals and high-performance air-entraining agent into the marine engineering concrete, and evenly form pores inside the concrete, which effectively solves the problem of high apparent density of concrete and reduces the concrete bulk density. The modified super absorbent resin ice crystals can not only strengthen the pore wall and reduce the loss of compressive strength and durability performance due to pore formation and air entrainment, but also can continuously provide sufficient moisture maintenance for the internal structure of the concrete for a long time, and can ensure that the concrete strength meets the design requirements in combination with short-term steam maintenance, thereby shortening the preparation period. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] Example 1 This embodiment provides a lightweight marine engineering concrete doped with modified super absorbent resin ice crystals, which is prepared by the following steps: Preparation of modified superabsorbent resin ice crystals S100, pouring the super absorbent resin particles into deionized water and stirring for 20 min to allow them to fully absorb water and swell to obtain a solution with a gel, and separating and removing the remaining deionized water in the solution to obtain a super absorbent resin gel; S101, in a low-temperature laboratory at room temperature of -5 to 0°C, evenly spread the super absorbent resin gel on the surface of a fine grid, put it into a freezing device and freeze it for 8 hours, and after the freezing, perform mechanical vibration dispersion to obtain super absorbent resin ice crystals; S102. In a low-temperature laboratory at a room temperature of -5 to 0°C, pour the super absorbent resin ice crystals into a modifier, rotate and stir for 10 min, and filter to obtain the modified super absorbent resin ice crystals.

[0023] In an embodiment of the present invention, preferably, in step S100, the ratio of the added amount of the super absorbent resin particles to the deionized water is 2:1200 in parts by weight; in step S102, the ratio of the added amount of the super absorbent resin ice crystals to the modifier is 2:7 in parts by weight.

[0024] In the embodiments of the present invention, preferably, the anionic surfactant is sodium dodecyl sulfate with a solid content of 0.5%; the interface enhancer is a solution-type interface enhancer; and the purity of the nano-silicon dioxide is 99.5%.

[0025] In the embodiment of the present invention, preferably, the weight ratio of the anionic surfactant, the interfacial enhancer and the nano-silicon dioxide is 0.2:200:3.

[0026] In an embodiment of the present invention, preferably, the weight ratio of the super absorbent resin, deionized water and modifier is 2:500:5; wherein, only the weight of the deionized water and modifier absorbed and adsorbed by the super absorbent resin is calculated.

[0027] Preparation of lightweight marine concrete doped with modified superabsorbent resin ice crystals S200, in a low temperature laboratory at room temperature of -5~0°C, 350 parts by weight of cement, 150 parts by weight of ultrafine powder and 20 parts by weight of stone powder were mixed uniformly to obtain a mixture A, 800 parts by weight of coarse aggregate and 700 parts by weight of fine aggregate were mixed uniformly to obtain a mixture B, 9 parts by weight of a high performance water reducing agent, 1.5 parts by weight of a high performance air entraining agent and 130 parts by weight of water were mixed uniformly to obtain a mixed solution C, and 50 parts by weight of modified super absorbent resin ice crystals were weighed; S201. In a low-temperature laboratory at a room temperature of -5 to 0°C, mix mixture A and mixture B, stir for 20 seconds, then pour into mixture C, stir for 240 seconds, and finally pour into modified superabsorbent resin ice crystals, stir for 30 seconds to obtain a mixture with an expansion of 420 mm; S202. In a low-temperature laboratory with a room temperature of -5 to 0°C, pour the mixture into a fixed mold, vibrate and roll it, seal the upper layer with a film, put it into a steam curing box at 80°C for curing after hardening, and then put it in a natural environment for curing to obtain the lightweight marine concrete doped with modified highly absorbent resin ice crystals.

[0028] In this embodiment, preferably, the cement is P·O 52.5 cement; the ultrafine powder is a mixed and refined product of fly ash, slag powder and silica fume, with a particle size of 0.1-30 μm; the stone powder is a mixed product of limestone powder and ceramic polishing powder, with a calcium carbonate content of 87%, a fineness of 8%, a 28d activity index of 95%, and a fluidity ratio of 99%; the coarse aggregate is a mixture of crushed stone with a particle size of 5-10 mm and crushed stone with a particle size of 10-20 mm in a weight ratio of 2:8, and the apparent density is 2650 kg / m 3 , the porosity is 40%, the crushing value is 2%; the fine aggregate is machine-made sand, the fineness modulus is 2.6, and the apparent density is 2600 kg / m 3 , the porosity is 41% and the crushing value is 23%.

[0029] In this embodiment, preferably, the high-performance water reducer is Point-VS304, a polycarboxylic acid high-performance water reducer (viscosity reducing type), which is compounded from polycarboxylic acid viscosity reducing water reducing mother liquor, a slump retaining agent, cellulose, a coagulant, a regulator and water, with a solid content of 13%, a water reduction rate of 27%, and a 28d compressive strength ratio of 145%.

[0030] In this embodiment, preferably, the high-performance air-entraining agent is an amphoteric air-entraining agent.

[0031] Example 2 This embodiment provides a lightweight marine engineering concrete doped with modified super absorbent resin ice crystals; wherein, in step S200, in mixture A, the addition amount of cement is 270 parts by weight, the addition amount of ultrafine powder is 200 parts by weight, and the addition amount of stone powder is 30 parts by weight; in mixture B, the addition amount of coarse aggregate is 800 parts by weight, and the addition amount of fine aggregate is 700 parts by weight; in mixed liquid C, the addition amount of high-performance water reducer is 11 parts by weight, the addition amount of high-performance air entraining agent is 2 parts by weight, the addition amount of water is 125 parts by weight, and the addition amount of modified super absorbent resin ice crystals is 70 parts by weight; in step S201, the expansion degree of the obtained mixture is 400 mm. The remaining raw materials, proportions and preparation steps are the same as those in Example 1.

[0032] Example 3 This embodiment provides a lightweight marine engineering concrete doped with modified super absorbent resin ice crystals; wherein, in step S200, in mixture A, the addition amount of cement is 350 parts by weight, the addition amount of ultrafine powder is 150 parts by weight, and the addition amount of stone powder is 20 parts by weight; in mixture B, the addition amount of coarse aggregate is 700 parts by weight, and the addition amount of fine aggregate is 800 parts by weight; in mixed liquid C, the addition amount of high-performance water reducer is 5 parts by weight, the addition amount of high-performance air entraining agent is 0.6 parts by weight, the addition amount of water is 140 parts by weight, and the addition amount of modified super absorbent resin ice crystals is 50 parts by weight; in step S201, the expansion degree of the obtained mixture is 430 mm. The remaining raw materials, proportions and preparation steps are the same as those in Example 1.

[0033] The present invention also provides the following comparative examples 1 to 4 for preparing a marine engineering concrete: Comparative Example 1 The difference between this comparative example and Example 1 of the present invention is that the modified super absorbent resin ice crystals are replaced with fine aggregate in equal amounts, and the addition amount of the high-performance air entraining agent is adjusted to 1.9 parts by weight. The remaining raw materials, proportions and preparation steps are the same as those of Example 1.

[0034] Comparative Example 2 The difference between this comparative example and Example 1 of the present invention is that the modified super absorbent resin ice crystals are replaced with super absorbent resin gel in equal amounts, that is, the super absorbent resin is not subjected to ice crystallization and modification treatment, and the addition amount of the high-performance air entraining agent is adjusted to 1.8 parts by weight. The remaining raw materials, proportions and preparation steps are the same as those of Example 1.

[0035] Comparative Example 3 The difference between this comparative example and Example 1 of the present invention is that the modified super absorbent resin ice crystals are replaced with super absorbent resin ice crystals in equal amounts, that is, the super absorbent resin is not modified. The remaining raw materials, proportions and preparation steps are the same as those of Example 1.

[0036] Comparative Example 4 The difference between this comparative example and Example 1 of the present invention is that the vibration roller forming and steam curing in step S202 are replaced by ordinary vibration forming and standard curing, that is, in this comparative example, step 202 is: in a low-temperature laboratory with a room temperature of -5~0°C, the mixture is poured into a fixed mold, vibrated and formed, the upper layer is sealed with a film, and standard curing is performed to obtain the marine engineering concrete; wherein, the standard curing is: after the strength of the specimen reaches the demolding standard, the mold is removed, and the demolded specimen is immediately placed in a standard curing room with a temperature of 20±2°C and a relative humidity of ≥95% for curing, or immediately placed in a non-flowing saturated calcium hydroxide solution with a temperature of 20±2°C for curing, and the specimens in the standard curing room should be placed on a bracket with a spacing of 10~20 mm from each other, and the surface of the specimen should be kept moist, but the specimen should not be directly rinsed with water. The remaining raw materials, proportions and preparation steps are the same as in Example 1.

[0037] The lightweight marine concrete doped with modified super absorbent resin ice crystals prepared in the above Examples 1 to 3 and the marine concrete prepared in the above Comparative Examples 1 to 4 were tested for performance in accordance with GB / T 50080-2016 Standard Test Method for Performance of Ordinary Concrete Mixtures and GB / T 50081-2019 Standard Test Method for Physical and Mechanical Properties of Concrete; the test results are listed in Table 1, where slump and expansion are the properties of fresh concrete mixtures, dry apparent density is the unit volume mass of concrete 60 days after demolding, and 60d compressive strength and 60d chloride ion migration coefficient respectively represent the compressive strength and chloride ion migration coefficient of concrete after 60 days.

[0038] Table 1 Performance test table of marine engineering concrete prepared in Examples 1 to 3 and Comparative Examples 1 to 4

[0039] According to the performance test data of Examples 1 to 3 in Table 1, within the specified material quantity range, by controlling the amount of modified superabsorbent resin ice crystals and air entraining agent, the concrete bulk density can be controlled at 2250 kg / m 3 About, reduce bulk density by 200kg / m 3 , achieving the effect of lightweight, and other performances can meet the requirements. This is because the modified super absorbent resin ice crystals are evenly distributed inside the concrete, forming a large number of microporous structures, among which the ice crystals of super absorbent resin can continue to melt during the cement hardening process, and the water is slowly absorbed by the pore wall, which promotes the full hydration of the concrete internal slurry structure, thereby improving the slurry quality, and the modification treatment can make the modifier act on the micropore wall, enhance the pore wall strength, thereby improving the mechanical properties and durability of the concrete.

[0040] Compared with Example 1, the slump and expansion of the marine engineering concrete prepared in Comparative Example 1 are smaller, the 60d compressive strength is significantly reduced, the 60d chloride ion migration coefficient is high, and the chloride ion penetration resistance is poor. Comparative Example 1 does not incorporate modified superabsorbent resin ice crystals. In order to keep the dry apparent density unchanged, the air entrainment amount of the concrete needs to be increased, that is, the amount of high-performance air entraining agent added is increased, indicating that the modified superabsorbent resin ice crystals can reduce the apparent density of concrete, and at the same time have a significant enhancement effect on the compressive strength and chloride ion penetration resistance of concrete.

[0041] Compared with Example 1, Comparative Example 2 uses a pre-absorbent super absorbent gel, and the super absorbent is not subjected to ice crystallization and modification treatment. This method has little effect on the apparent density of concrete. In order to keep the dry apparent density unchanged, it is still necessary to increase the amount of air entraining agent to achieve pore formation; further, according to the data in Table 1, the slump and expansion of the concrete in Comparative Example 2 increase. This is because the water absorption rate of the super absorbent resin in water is much greater than that in a strong alkaline solution, and the cement paste is a strong alkaline system. During the mixing process of the super absorbent resin that has not been ice-crystallized with the cement paste, water will precipitate from the super absorbent resin and merge with the paste, causing the expansion to increase; in addition, the 60d compressive strength of the marine engineering concrete prepared in Comparative Example 2 is smaller than that in Example 1, and the chloride ion migration coefficient is higher than that in Example 1, indicating that the super absorbent gel can be used as an internal curing agent for the concrete to provide water for subsequent hydration and improve the strength of the concrete internal paste, but due to the increase in the water-cement ratio, the concrete strength will decrease instead.

[0042] Comparative Example 3 Compared with Example 1, Comparative Example 3 uses unmodified super absorbent resin ice crystals. According to the data in Table 1, the 60d compressive strength of the concrete decreases, but the decrease is smaller than that in Comparative Example 2, and the chloride ion migration coefficient increases, indicating that the ice crystallization treatment can effectively adjust the changing trend of the water-cement ratio inside the concrete, thereby reducing the impact on the strength of the concrete, and the super absorbent resin forms tiny pores inside the concrete, which can effectively reduce the concrete bulk density. Further, it also shows that the modification treatment can effectively improve the pore structure and slurry quality.

[0043] Compared with Example 1, Comparative Example 4 uses conventional molding and standard curing mode. The dry apparent density of concrete increases, the 60d compressive strength decreases, and the 60d chloride ion migration coefficient decreases, indicating that during the ordinary hardening molding and curing process, the internal pores and slurry structure of the concrete are changed. For the low water-binder ratio formula, the modified highly absorbent resin ice crystals are used for internal water supply, and no external curing is required. It can be cured in the natural environment by short-term steam curing, which significantly shortens the production period.

[0044] Although the terms such as lightweight marine concrete, super absorbent resin gel, super absorbent resin ice crystal, modified super absorbent resin ice crystal, modifier, high performance water reducing agent, high performance air entraining agent, uniform paving, vibration dispersion, vibration forming, roller pressing, steam curing, standard curing, bulk density, pore making, etc. are used more frequently in this article, the possibility of using other terms is not excluded. The use of these terms is only for more convenient description and explanation of the essence of the present invention; interpreting them as any additional limitation is contrary to the spirit of the present invention.

[0045] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A modified super absorbent resin ice crystal, characterized in that: It is made by super absorbent resin particles absorbing water and expanding, then freezing to form ice crystals, and then adsorbing and modifying with a modifier; The ratio of the super absorbent resin, deionized water and modifier by weight is (2-5): (500-1200): (5-12), wherein only the weight of the deionized water and modifier absorbed and adsorbed by the super absorbent resin is calculated; The modifier is obtained by mixing an anionic surfactant, an interfacial enhancer and nano silicon dioxide in a weight ratio of (0.1-0.5): (100-300): (1-10).

2. The modified super absorbent resin ice crystal according to claim 1, characterized in that: The particle size of the super absorbent resin particles is 0.01-1 mm; The anionic surfactant is any one of sodium lauryl sulfate, sodium lauryl polyoxyethylene ether sulfate and sodium α-olefin sulfonate, and the solid content is 0.2% to 0.7%; The interface enhancer is an emulsion-type interface enhancer or a solution-type interface enhancer; The nano silicon dioxide has a particle size of 50-100 nm and a purity of ≥98%.

3. The modified super absorbent resin ice crystal according to claim 1, characterized in that: The preparation process is: S100, pouring the super absorbent resin particles into deionized water and stirring them sufficiently to allow them to fully absorb water and swell to obtain a solution with a gel, and separating and removing the remaining deionized water in the solution to obtain a super absorbent resin gel; S101, in a low-temperature laboratory at room temperature of -5 to 0°C, evenly spread the super absorbent resin gel on the surface of a fine grid, put it into a freezing device and freeze it for 6 to 10 hours, and after the freezing, perform mechanical vibration dispersion to obtain super absorbent resin ice crystals; S102. In a low-temperature laboratory at a room temperature of -5 to 0°C, pour the super absorbent resin ice crystals into a modifier, rotate and stir for 2 to 10 minutes, and filter to obtain the modified super absorbent resin ice crystals.

4. The modified super absorbent resin ice crystal according to claim 3, characterized in that: In step S100, the ratio of the addition amount of the super absorbent resin particles to the deionized water is (2-5): (1200-2000) in parts by weight; In step S102, the ratio of the added amount of the super absorbent resin ice crystals to the modifier is (1-5): (3-10) in parts by weight.

5. A method for preparing lightweight marine engineering concrete using the modified super absorbent resin ice crystals doped with the modified super absorbent resin ice crystals as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: S200. In a low-temperature laboratory at a room temperature of -5 to 0°C, cement, ultrafine powder and stone powder are mixed uniformly by weight to obtain a mixture A, coarse aggregate and fine aggregate are mixed uniformly to obtain a mixture B, a high-performance water reducing agent, a high-performance air entraining agent and water are mixed uniformly to obtain a mixed solution C, and modified superabsorbent resin ice crystals are weighed; S201. In a low-temperature laboratory at a room temperature of -5 to 0°C, mix mixture A and mixture B, stir for 10 to 30 seconds, then pour into mixture C, stir for 180 to 240 seconds, and finally pour into modified superabsorbent resin ice crystals, stir for 20 to 40 seconds to obtain a mixture with an expansion range of 450 to 500 mm; S202. In a low-temperature laboratory at a room temperature of -5 to 0°C, pour the mixture into a fixed mold, vibrate and roll it, seal the upper layer with a film, and after hardening, put it into a steam curing box at 80 to 90°C for curing for 0.5 to 1 day with the mold, and then place it in a natural environment for curing to obtain the lightweight marine concrete doped with modified highly absorbent resin ice crystals.

6. The method for preparing lightweight marine engineering concrete doped with modified super absorbent resin ice crystals according to claim 5, characterized in that: The distribution ratio of each group is as follows: 270~350 parts of cement 45~70 parts of modified super absorbent resin ice crystal Ultrafine powder 150~200 parts 20~30 parts of stone powder Coarse aggregate 700~800 parts Fine aggregate 700~800 parts High performance water reducing agent 5~11 parts High performance air entraining agent 0.6~2 parts 125~140 parts of water.

7. The method for preparing lightweight marine engineering concrete doped with modified super absorbent resin ice crystals according to claim 5, characterized in that: The cement is any one of P·O 42.5R cement, P·O 52.5 cement and P·II 52.5 cement; The ultrafine powder is a mixed and refined product of various mineral admixtures after grinding, and the particle size is 0.1-30 μm. The mineral admixture is any two or a combination of any two of fly ash, slag powder, silica fume and microbeads; The stone powder is any one of limestone powder, marble powder, granite powder and ceramic polishing powder or any combination thereof, and the stone powder has a calcium carbonate content of 82% to 87%, a fineness of 8% to 13%, a 28d activity index of 80% to 95%, and a fluidity ratio of 97% to 103%; The coarse aggregate is any one of crushed stone with a particle size of 5-10 mm, crushed stone with a particle size of 5-16 mm, crushed stone with a particle size of 5-20 mm, and crushed stone with a particle size of 10-20 mm, or any combination thereof, and the apparent density of the coarse aggregate is 2650-2670 kg / m 3 , the porosity is 39%~42%, and the crushing value is 2%~4%; The fine aggregate is machine-made sand with a fineness modulus of 2.5-2.8 and an apparent density of 2590-2630 kg / m 3 The porosity is 40%~44% and the crushing value is 20%~25%.

8. The method for preparing lightweight marine engineering concrete doped with modified super absorbent resin ice crystals according to claim 5, characterized in that: The high-performance water reducer is compounded from polycarboxylic acid viscosity-reducing water-reducing concentrate, a slump-retaining agent, cellulose, a coagulant, a regulator and water, and has a solid content of 12% to 15%, a water reduction rate of 25% to 30%, and a 28d compressive strength ratio of 140% to 150%.

9. The method for preparing lightweight marine engineering concrete doped with modified super absorbent resin ice crystals according to claim 5, characterized in that: The high-performance air-entraining agent is any one of anionic air-entraining agent, cationic air-entraining agent, non-ionic air-entraining agent and amphoteric air-entraining agent, or a combination of any several of them.

10. A lightweight marine engineering concrete doped with modified super absorbent resin ice crystals, characterized in that: The lightweight marine concrete is prepared by the preparation method of the lightweight marine concrete doped with modified super absorbent resin ice crystals as described in any one of claims 5 to 9.

Citation Information

Cited By

  • Manufacturing method for lightweight cement and its applications in building material structures, bamboo-reinforced lightweight cement structures, and marine construction structures

    TWI927764B